Hubungan Kadar Gula Darah dengan Nilai Ankle Brachial Index Pasien Diabetes Melitus di Out Patient Departement Siloam Hospital Denpasar - Susiyanti, Erna; Laksmi, Ida Ayu Agung; Dewi, Putu Adi Cahya; Wijaya, I Putu Artha (Faculty of Medicine, Universitas Andalas, 2025)
Uncontrolled blood sugar levels in patients with diabetes mellitus will result in peripheral neuropathy in the lower extremities, so that the sensitivity of the feet will decrease. Ankle Brachial Index (ABI) assessment is necessary for Type 2 Diabetes Mellitus (T2DM) patients to detect peripheral neuropathy early, particularly on the soles of the feet. Low ABI values that cause vascular disorders are influenced by increasing age, duration of DM and obesity. Objective: To determine the relationship between blood sugar levels and the ankle brachial index value of patients with diabetes mellitus in the Out-Patient Department (OPD) Siloam Hospital, Denpasar. Methods: This study employed a correlational research design with a cross-sectional approach, using simple random sampling to involve 227 respondents. The research instruments used were a Sphygmomanometer to measure the ABI value and a Glucometer (Glukotest) to measure the blood sugar levels of respondents. Data analysis was carried out using Spearman's rank correlation. Results: Based on the value of blood sugar levels, it shows that the majority of respondents have a high category, namely 205 respondents (90.3%) and based on the value of the ankle brachial index (ABI), the majority of respondents' right foot ABI values are in the mild obstruction category, namely 128 respondents (56.4%) and the majority of the left foot has mild obstruction, namely 133 respondents (59.5%). The analysis yielded a p-value of 0.001, indicating a significant relationship between blood sugar levels and ankle brachial index (ABI) values. Conclusion: There is a significant relationship between blood sugar levels and ABI index on T2DM. Keywords: ankle brachial index, blood sugar level, T2DM